2006
DOI: 10.1158/1078-0432.ccr-05-1858
|View full text |Cite
|
Sign up to set email alerts
|

Stomatin-like Protein 2 Is Overexpressed in Cancer and Involved in Regulating Cell Growth and Cell Adhesion in Human Esophageal Squamous Cell Carcinoma

Abstract: Purpose: Stomatin-like protein 2 (SLP-2) is a novel and unusual stomatin homologue of unknown functions. It has been implicated in interaction with erythrocyte cytoskeleton and presumably other integral membrane proteins, but not directly with the membrane bilayer.We show here the involvement of SLP-2 inhuman esophageal squamous cell carcinoma (ESCC), lung cancer, laryngeal cancer, and endometrial adenocarcinoma and the effects of SLP-2 on ESCC cells. Experimental Design: Previous work of cDNA microarray in ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
101
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 21 publications
6
101
0
1
Order By: Relevance
“…Phylogenic analysis revealed that SLP-2 was acquired through the mitochondrial endosymbiosis and belongs to a different lineage than other stomatin-like proteins [21]. SLP-2 is highly expressed in several types of human tumors [22], and high SLP-2 levels are associated with decreased survival of patients suffering from primary invasive breast cancer [23], suggesting a role for SLP-2 in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenic analysis revealed that SLP-2 was acquired through the mitochondrial endosymbiosis and belongs to a different lineage than other stomatin-like proteins [21]. SLP-2 is highly expressed in several types of human tumors [22], and high SLP-2 levels are associated with decreased survival of patients suffering from primary invasive breast cancer [23], suggesting a role for SLP-2 in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Western Blot-Western blots were performed as previously described (37). Protein bands were detected by chemiluminescence using the ECL system (Vigorous Biotech, Beijing, China) according to the manufacture's protocol.…”
mentioning
confidence: 99%
“…Moreover, a luciferase reporter assay indicated that SLP-2 regulates MMP-9 expression in an NF-jB-dependent manner, suggesting that SLP-2 may be a component of the NF-jB signaling pathway [14]. Consistent with this possibility, fibronectin 1, a downstream target of NF-jB, is downregulated following SLP-2 knockdown in ESCC cells, and fibronectin 1 and SLP-2 expression levels are significantly correlated in ESCC tissues [9]. Future studies to determine the cellular mechanisms by which SLP-2 promotes GC progression are warranted.…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that stomatins are involved in the organization of the peripheral cytoskeleton, the formation of sphingolipid-and cholesterolrich lipid rafts, and the assembly of ion channels and mechanosensation receptors [19,20]. SLP-2 expression is upregulated in multiple tumor types, including ESCC, endometrial adenocarcinoma, LSCC, breast cancer, PSCC, and glioma [4,[9][10][11][12][13][14], but the mechanisms leading to SLP-2 overexpression in human tumors are not well known. SLP-2 has been shown to enhance invasiveness in glioma cells, potentially through the upregulation of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation